Problems of determining the borrower's creditworthiness - Oleksii Miroshnyk; Svitlana Shubina; Valeriia Shulha (Фінансово-кредитні системи: перспективи розвитку., 2023)
This article addresses the challenges associated with determining the borrower's creditworthiness. The authors define the borrower's creditworthiness as the ability to timely and fully meet debt obligations to the lender. This determination is based on an evaluation of the borrower's financial condition, forecast of business development, and other factors influencing the ability to repay the loan.